Right Atrial Myxoma Mimicking Dilated Cardiomyopathy with Right Ventricular Dysfunction in a 15-Year-Old Girl: A Case Report - Efe Abolodje; Nicholas Kogha; Elohor Boyo (International Journal of Medicine and Health Development, 2025)
Atrial myxoma is commonly misdiagnosed due to non-specific and variable clinical presentation. A 15-year-old girl who presented with features of heart failure with echocardiogram findings of dilated cardiomyopathy eventually proved to be right atrial myxoma. Surgical intervention was declined due to severely poor LV function. There is a need to carry out further research that may provide non-surgical treatment for patients not operable.